Effects of Gibberellin (GA3) Concentration and Immersion Time of Various Cuttings On The Germination of Mangosteen Seeds (Garcinia mangostana L)MBAHAN BENIH MANGGIS (Garcinia mangostana L) - Dede Suhendra; T. Chairun Nisa; Diana Sofia Hanafiah (Talenta Publisher, 2016)
The purpose of this study is to determine the best number of seeds cuttings, gibberellin concentration and immersion time for the germination of mangosteen seeds. This research conducted at Laboratory of Seed Technology Faculty Agriculture, University of Sumatera Utara, Medan from December to March 2016. Experimental design used a factorial randomized block design with three factors, seed cutting, gibberellin concentrations and immersion time. Parameters measured were membrane leakage (μmhos), normal seedling (%), abnormal seedling (%), died seeds (%), germination rate (days), vigor Index (%). The results show that intact mangosteen seeds or without cutting, application of gibberellin at a concentration of 75 ppm and 24 hours time immersion are the best treatments to mangosteen seed germination.